The Analysis of Robinson Crusoe in Terms of Halliday's Modality - Amed Hamadi, Dhuha (International Journal of Psychosocial Rehabilitation, 2020)
The study analyzes modality markers with their values that are introduced by M.A.C. Halliday as a part of the Systemic-Functional Grammar Approach. Modality types (modalization and modulation) are linguistically applied to a number of categories, namely obligation, permission, prohibition, necessity, possibility, and ability. This study aims to show how modality is used in practice to express ideas about certainty and uncertainty. Moreover, the modality values are used to show how the writer strongly presents his attitudes to the readers to express certainty or uncertainty. The data of the study is D. Defoe's novel, Robinson Crusoe. The analysis results indicate that modality is lexico-grammaticalized in literary narratives in a variety of modes, of which the modalization expressions are of high frequency, especially probability, which is highly utilized. Plus, the writer utilizes the median value with a high proportion among the other types to reveal the objectivity and credibility in presenting his propositions/proposals to his readers.